1998
DOI: 10.1007/s004420050376
|View full text |Cite
|
Sign up to set email alerts
|

Plant species-specific changes in root-inhabiting fungi in a California annual grassland: responses to elevated CO 2 and nutrients

Abstract: Five co-occurring plant species from an annual mediterranean grassland were grown in monoculture for 4 months in pots inside open-top chambers at the Jasper Ridge Biological Preserve (San Mateo County, California). The plants were exposed to elevated atmospheric CO and soil nutrient enrichment in a complete factorial experiment. The response of root-inhabiting non-mycorrhizal and arbuscular mycorrhizal fungi to the altered resource base depended strongly on the plant species. Elevated CO and fertilization alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 37 publications
4
37
1
Order By: Relevance
“…Although we presently do not have data on specific fungal communities in our experiment, an increase in N-acetylglucosaminidase activity under elevated CO 2 may result from a greater production of fungal cell wall litter (Miller et al, 1998). This would be consistent with other studies that have observed greater mycorrhizal infection (%), and higher levels of mycorrhizal and saprophytic fungal biomass under elevated CO 2 (Rillig et al, 1998;Klironomos et al, 1996). N-acetylglucosaminidase in our study displayed a nearly twofold increase with elevated CO 2 (Fig.…”
Section: Metabolism Of Root-derived Substratesupporting
confidence: 93%
“…Although we presently do not have data on specific fungal communities in our experiment, an increase in N-acetylglucosaminidase activity under elevated CO 2 may result from a greater production of fungal cell wall litter (Miller et al, 1998). This would be consistent with other studies that have observed greater mycorrhizal infection (%), and higher levels of mycorrhizal and saprophytic fungal biomass under elevated CO 2 (Rillig et al, 1998;Klironomos et al, 1996). N-acetylglucosaminidase in our study displayed a nearly twofold increase with elevated CO 2 (Fig.…”
Section: Metabolism Of Root-derived Substratesupporting
confidence: 93%
“…rubens and Schismus barbatus, have recently invaded portions of the Mojave and Sonoran Deserts (Pake et al 1995, Brooks 1999, Holzapfel and Mahall 1999, Brooks 2003. Field experiments have shown that these grasses are highly responsive to elevated soil N, more so than most native species (Rillig et al 1998, DeFalco et al 2001, Brooks 2003. The recent increases in N deposition are correlated with the increased productivity of these grasses.…”
Section: Nitrogen Deposition Enhances Nonnative Species Invasionsmentioning
confidence: 99%
“…It is generally assumed that the CO 2 -induced increases in soil C availability will increase fungal biomass more than bacterial biomass (Klironomos et al 1996;Rillig et al 1998). Indeed, Jones et al (1998) observed increases in fungal abundance in response to elevated CO 2 .…”
Section: Effects Of Elevated Co 2 On the Microbial Communities In Thementioning
confidence: 99%